Alley cropping in the moist savanna of West Africa I. Restoration and maintenance of soil fertility on terre de barre soils in Benin Republic - Aihou, K.; Sanginga, N.; Vanlauwe, Bernard; Lyasse, O.; Diels, J.; Merckx, Roel (1999)
The potential of alley cropping systems supplied with a limited amount of fertilizer to restore crop productivity on a degraded site and to maintain crop productivity on a recently cleared, non-degraded site on ‘terre de barre' soils in Southern Bénin was investigated from 1994 to 1996. Leucaena leucocephala, Senna siamea and Gliricidia sepium were used as hedgerow species. Maize yields of the no-tree control plots dropped from the initial (1990) 401 kg ha–1 and 2181 kg ha–1 on the degraded and non-degraded sites, respectively, to 109 kg ha–1 and 1346 kg ha–1 in 1996, even with application of a minimal amount of mineral fertilizer. The alley cropping systems produced on average (mean of three treatments and three years) 107% more grain than the initial 1990 values on the degraded site and 11% less grain than the initial 1990 values on the non-degraded site. Especially the Senna and to a lesser degree the Leucaena treatment yielded consistently more grain than the control. The Senna trees contained a larger amount of N and produced more wood during the first pruning on the degraded site (155 kg N ha–1 and 14.0 ton fresh wood ha–1) than on the non-degraded site (49 kg N ha–1 and 6.6 ton fresh wood ha–1) most likely because of differences in subsoil fertility, as indicated by the higher clay, exchangeable bases, and N content between 60 and 125 cm cm. N accumulation and wood production by the Leucaena and Gliricidia trees was similar in both sites (82 and 36 kg N ha–1 and 4.6 and 9.3 ton fresh wood ha–1, respectively). When a limited amount of fertilizer is available, Senna appears to be the best choice as hedgerow species on sites with a relatively fertile subsoil. For other soils, a N2-fixing species may be a better choice.